THE MEDIATING ROLE OF KNOWLEDGE SHARING IN THE RELATIONSHIP BETWEEN LEADER-MEMBER EXCHANGE AND WORK INTEGRATION (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: The purpose of this study is to explain the mediating effect of knowledge sharing (KS) between leader-member exchange (LMX) and work integration (WI) on healthcare workers. The study also examines the direct effects of LMX on WI among selected healthcare workers in Türkiye.Methodology: The study targeted a sample of N = 295 to provide relevant information. The data were collected using an adopted questionnaire, including LMX (Baş et al., 2010), KS (Chennamaneni et al., 2012), and WI (Schaufeli et al., 2002). A purposive stratified sampling method was used since the participants were considered based on predefined criteria. The study used a 5-point Likert scale ranging from 1= strongly disagree to 5= strongly agree. SPSS 22.0 and AMOS 17.0 packages were used for data analysis and interpretation of statistical outputs.Results: The study revealed a significant positive relationship between variables. Goodness of fit values of the scales were also checked. First, the mediating variable (knowledge sharing) between LMX and WI was investigated. Second, the effect of LMX on WI was explored. Based on the findings, a significant positive relationship was found between the variables of the study.Conclusion: According to the research results, significant relationships were found between LMX and WI, between LMX and KS, and between KS and WI. In addition, it was determined that knowledge sharing had a mediating role in the effect of LMX on WI, which was the main purpose of the research. According to the research results, high-quality LMX relationships enable employees to be more open to KS and to integrate more into their work. In this case, KS acts as a bridge that strengthens the link between LMX and WI. Employees find greater meaning in their work by sharing their knowledge, which in turn increases their commitment to it. As a result, leaders creating a culture that supports knowledge sharing can be seen as an effective way to increase work integration and improve organizational performance.